Exploring the design of online content for e-learning / Soo Kum Yoke ... [et al.] - Soo, Kum Yoke; Hasan, Nor Haniza; Syed Ahmad, Tuan Sarifah Aini; Ismail, Noriah; Zainon, Saunah; Abdullah, Mohammad (2021)
Due to the uncertain state of the Covid-19 pandemic, the education system has been thrown off-guard and ill-prepared to cope with online lessons. As such, this paper aims to explore the online learning experience of both instructors and learners in a situation where they have to continue teaching and learning sessions without face-to-face contact. The paper explores the different models for designing e-learning content and the pedagogical benefits and challenges that has to be considered for the disseminating of knowledge and information. Inadequacies of offline content have also been researched. Finally, the study puts forth recommendations as to whether online contents can be used for e-learning